The Stateless Person In Indonesia: Consequences and Legal Protection - Nurmawati, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 1 (2022), 2022)
This study aimed to examine what the legal consequences are for those who are stateless persons and how the government's legal protection for people with status as stateless persons in Indonesia. The method used to achieve this goal is through normative legal research. Legal materials will be collected by means of an inventory, classification, identification, interpretation and descriptive analysis. The results indicated that there are various causes of statelessness, such as: disintegration of the nation, political factors, the application of different citizenship principles between countries, bureaucratic obstacles, racial, religious discrimination and etcetera. The state of statelessness will result in the lack of rights and obligations and protection of them from any country. Indonesia has attempted to provide legal protection for those with statelessness through concrete efforts by collaborating with UNHCR, entering into agreements between countries, discretion and regulations in existing legislation. However, the existing regulations still need to be revised the obscurity of several norms relating to protection of stateless persons.